Enrobing Ceremony for Judges Thomas Harris, Steven Vartabedian, Edward Sarkisian, Jr. and Lawrence Jones at Fresno's Veterans Memorial Auditorium - Watkins, Howard::::::::: (1987)
Judge Dwayne Keyes and former District Attorney Clark Savory Clark Savory appointed DA 1950 following death of James Thuesen, served until retirement in 1966